THE POLICY OF CONSUMER PROTECTION IN THE ELECTRICITY MARKET - Filipović, Sanja; Tanić, Gordan (Economic Annals, 2008)
The provision of a safe and reliable electricity supply has a central place in modern social life. The rise of electricity prices and the process of liberalisation of the electricity market are the two main factors which have made it necessary to modify the current traditional ways of protecting vulnerable customer categories. The Internal Energy Market Directives provisions ensure that citizens have access to energy of a specified quality level at reasonable, cost-reflective prices and to the conditions of real competition and free choice. This objective implies intervention due to the fact that some consumer classes are less attractive for the companies (remote consumers, low consumption consumers or low-income consumers). The aim of this paper is to analyze the current forms of vulnerable customer protection from the critical point of view and to point out possibilities for their application in the case of Serbia.